Relationship between organizational culture and organizational commitment: the study of Malaysia Nasional News Agency (BERNAMA) - Ab Razak, Siti Nur Khairiyah (2011)
Research has suggested that understanding organization culture as a management philosophy is essential to managing an organization in improving its overall performance. Using questionnaire survey, this study examines the influence of organization culture on organizational commitment towards the Bernama staff. Specifically, this study examines four dimensions of organization culture, namely training and development, rewards and recognition, teamwork, and organization communication on employees’ commitment towards the organization. That’s all four dimensions as independent variable as stated on theoretical framework. From three types of commitment- Normative, Affective and Continuance commitment, this study only cover the continuance commitment as dependent variable. One hundred and nineteen respondents from a Malaysia National News Agency (Bernama) listed of staff participated in the survey. The results show that all dimensions of organization culture which stated in literature review are important determinants in motivating and influence the employees to be committed to their organization. The findings implicate that an organization needs to be aware of the importance of these dimensions in providing a favorable working environment to its employees in attaining their full commitment for organizational success. However, training and development and rewards and recognition show insignificant compare with the other two independent variable that shows a significant relationship in this study.